IMPLEMENTATION OF GROUP METHOD PROJECT IN INCREASING MATHEMATICAL EXPERIENCES - Husein, Ismail (ZERO: Jurnal Sains, Matematika dan Terapan, 2018)
Mathematics as a vehicle for education has the purpose of educating students, forming the personality of students, and developing certain skills so that they can direct students to learning values in life through mathematics. One of the fundamental problems in education in Indonesia is the lack of students who can understand mathematical concepts well. One method that promises to reduce this problem is the group project method.